Eksistensi Makna Filsafat dan Objek Kajiannya Dalam Pendidikan Islam - Zikri Adib Kurnia; Eva Sariwati Tampubolon; Imam Muslimin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
Philosophy is a deep and systematic scientific discipline that aims to understand and explain various aspects of life. In the context of Islamic education, philosophy not only focuses on the transfer of knowledge, but also on the formation of students' character and morals. The purpose of this article is to find out the objects and studies of philosophy. There are 3 objects of philosophical study: First, ontology is an object of study that investigates the nature of reality and existence. Second, epistemology is an object of study that understands the sources and methods of knowledge. Third, axiology is a philosophy that studies values. The method used in this research is library research with an article review approach based on Harold Laswel's theory, with data collected using literature review procedures and analyzed using content analysis techniques. The results found are first, in terms of ontology. There are 7 ontological aspects of science, namely (a) Methodical, (b) Systematic, (c) Coherence, (d) Rational, (e) Comprehensive (f) Radical, (g) Universal. There are 7 schools of epistemology, namely Rationalism, Empiricism, Criticism, Positivism, Skepticism, Pragmaticism and Idealism, while in Islamic thought there are 3, namely Bayani, Irfani and Burhani. Third, there are 3 theories of axiology or values, namely Logic, Ethics and Aesthetics.